The Evolution of the Manitoba Optometry Act - Mintz, S (Canadian Journal of Optometry, 2021)
The history of optometric legislation in Manitoba is discussed. Beginning with the passage of the Optometry Act in 1909, the evolution of the Act is followed, culminating in landmark amendments in 1983.